FOOD IMPULSIVE BUYING AND PERSONAL NORMS AS PREDICTORS ON FOOD-WASTING BEHAVIOR IN ADOLESCENTS IN MAKASSAR CITY, INDONESIA - Radde, Hasniar Ambo; Indriyani Rachman; Toru Matsumoto (Lembaga Penelitian Universitas Pasundan, 2024)
Food-wasting behavior can occur when someone does not finish the food they have taken. It can also be seen in purchasing or taking more food than they can consume. Food-impulsive behavior and personal norms are assumed to predict food-wasting behavior, and this study aims to prove this assumption. Personal norms reflect an individual's personal value system in specific situations that can influence specific behaviors, while food impulsive behavior refers to consumers' tendency to buy impulsively, without reflection, immediately, and impulsively. This research was conducted in Makassar City on 150 adolescents aged 12 to 19 years old, and the data were analyzed using multiple linear regression. This study provides three findings. First, food-impulsive behavior and personal norms together can predict food wasting by 32.5% (p=0.000; p<0.05). Second, food-impulsive behavior positively predicts food-wasting behavior by 11% (p=0.000; p<0.05), indicating that the higher someone's food-impulsive behavior, the higher their food-wasting behavior. Third, personal norms can negatively predict food-wasting behavior by 21.5% (p=0.000; p<0.05), indicating that the higher someone's personal norms, the lower their food-wasting behavior.